1995
DOI: 10.1017/s001309150001909x
|View full text |Cite
|
Sign up to set email alerts
|

The fibre of a cell attachment

Abstract: In view of understanding the Hopf algebra structure of the loop space homology H t (Q{E (J/ e " + ')) in terms of H t (tlE) and the map /, we consider the homotopy fibre F of the inclusion map (o: E c» £ {J f e°+ 1 . In [15], the case when H t (Clo]) is surjective (the "inert" case) was studied, and in [11] a weaker condition, called "lazy", was considered. Here we give several new characterizations of inert and lazy cell attachments in terms of properties of F. We also show how these results extend to the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Then d 0 d 1 w ∈ (∧ 2 W ) k+2 and so d 0 d 1 w ∈ R ∧ ∧W ⊕ Qa 2 . Thus ϕ(d 0 d 1 w) = 0 and again by (17)…”
mentioning
confidence: 89%
“…Then d 0 d 1 w ∈ (∧ 2 W ) k+2 and so d 0 d 1 w ∈ R ∧ ∧W ⊕ Qa 2 . Thus ϕ(d 0 d 1 w) = 0 and again by (17)…”
mentioning
confidence: 89%
“…Determining the conditions under which θ is a Hopf Algebra isomorphism is called the cell attachment problem. This has a long history, having been studied by Anick [1], Bubenik [3], Félix and Thomas [5], and Halperin, Hess, and Lemaire [11,7,8,9]. Lemaire [11], for one, found that θ is a Hopf algebra isomorphism whenever the morphism of graded R-vector spaces induced by the canonical surjection H * (ΩX; R) π → H * (ΩX; R) I is bijective, and R is a vector space of characteristic p.…”
Section: Mod-p Loop Space Homologymentioning
confidence: 99%
“…This has a long history, having been studied by Anick [1], Bubenik [3], Félix and Thomas [5], and Halperin et al . [7][8][9]11]. Lemaire [11], for one, found that θ is a Hopf algebra isomorphism whenever the morphism of graded R-vector spaces Tor π p :…”
Section: Mod-p Loop Space Homologymentioning
confidence: 99%